Revitalizing Congregations: Refocusing and Healing Through Pastoral Transitions - Avery, William (Rowman & Littlefield Publishers, 2003)
Are congregations inevitably stuck during a change of pastoral leadership? Or are there ways they can take advantage of this interim to grow and set new directions? Researcher and seminary professor William Avery tells us the stories of six congregations (from different denominations, regions of the country, settings, sizes, and ethnic and racial makeup) that attempted to revitalize their mission during this critical time of change and transition. As Loren Mead explains in the foreword, however, Avery does not tell congregational leaders “the way” to transformation through an interim. Rather, he offers detailed snapshots of congregations and their leaders trying to work their way through this potentially difficult time. He also shows how a trained interim pastor can make a difference in the ensuing effectiveness of the congregation. “These are stories about how faithful congregations have attempted to build toward and discover a leadership model that works for them,” Mead says, “These are stories from which your congregation can learn much.”